A Study of Parents and Teachers Perceptions of Parent Involvement in Primary Schools in Mogadishu - Mohamed Abdullahi Gure (Universiti Sains Islam Malaysia, 2024)
There is almost a complete certainty among educators that parental involvement is the remedy for many of the problems facing schools. It is also widely acknowledged that school administrators and teachers have important roles in promoting parental involvement in children’s education. This work aims at examining the views of parents and teachers on school-partnership practices for promoting parental involvement in education in selected primary schools in Mogadishu-Somalia. Moreover, this study aims to identify the level of parental involvement in these selected schools. The method, which has been employed in this study, is a mixed-method approach; data was collected from parents as well as from teachers of the selected schools using survey questionnaires and interviews. A sample size of 377 parents and 214 teachers participated in this study. This study used two instruments that have been developed by Epstein and Salinas (1993) to assess the perceptions of parents and teachers about parental involvement. Furthermore, data were collected qualitatively through interviews with parents and teachers of the selected schools. For analyzing the data, this study used some statistical techniques including descriptive statistics such as means, percentages, and frequencies. Furthermore, this study used inferential statistics such as one-Way ANOVA and hierarchical multiple regression. The initial analysis of the qualitative data was guided by the quantitative results of this study. The findings of this study show that parents and teachers had similar positive perceptions towards school practices for parental involvement. The findings also show that the level of parents’ overall involvement in children’s educations was average. Furthermore, the results indicated that the variations in the level of parents’ involvement were significantly explained by their perceived school practices (student learning, communication and decision making) and their demographic characteristics particularly their level of education. This study is significant for several reasons. It contributes to the limited information on parental involvement in Somalia and therefore, filling a gap in the existing empirical literature. It offers information to educators as well as to parents, which will help them understand the issues that relate to parental involvement in education. It is hoped that information from this study will facilitate parents and teachers to understand each other’s ideas on parental involvement and develop positive working relations to support children to become successful in their education.